Ten-Minute Test for Differentiating Between Klebsiella and Enterobacter Isolates - Matsen, John M. (1970)
A 10-minute test, utilizing a urease paper-reagent strip (PATHO-TEC), for differentiating Klebsiella and Enterobacter species is described. By using a heavy suspension of organisms and 50 C temperature for incubation, 93% of Klebsiella strains (186/200) were positive and 95% of Enterobacter strains (190/200) were negative with this testing system. The rapid nature of the test (10 min), the facility with which it can be carried out, and the ease with which the strips can be stored and handled may make this a useful aid for the clinical microbiologist.